2013
DOI: 10.1111/jnc.12609
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐29b modulates Japanese encephalitis virus‐induced microglia activation by targeting tumor necrosis factor alpha‐induced protein 3

Abstract: Japanese encephalitis virus (JEV), a single-stranded RNA (ssRNA) virus, is the leading cause of encephalitis in Asia. Microglial activation is one of the key events in JEV-induced neuroinflammation. Although the various microRNAs (miRNAs) has been shown to regulate microglia activation during pathological conditions including neuroviral infections, till date, the involvement of miRNAs in JEV infection has not been evaluated. Hence, we sought to evaluate the possible role of miRNAs in mediating JEV-induced micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 51 publications
(121 reference statements)
2
80
0
Order By: Relevance
“…Thus, in this study, we aimed to address the role of miRNA-regulated pathways in the JEV-induced neuroinflammation model. Recently, the roles of miR-29b and miR-155 in microglial activation during JEV-induced neuroinflammation were studied (42,53,54). In this study, we demonstrated that miR-15b is stimulated both in vitro and in vivo, and miR-15b regulates the inflammatory response following JEV infection by targeting RNF125.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Thus, in this study, we aimed to address the role of miRNA-regulated pathways in the JEV-induced neuroinflammation model. Recently, the roles of miR-29b and miR-155 in microglial activation during JEV-induced neuroinflammation were studied (42,53,54). In this study, we demonstrated that miR-15b is stimulated both in vitro and in vivo, and miR-15b regulates the inflammatory response following JEV infection by targeting RNF125.…”
Section: Discussionmentioning
confidence: 70%
“…They also reported that miR-29b has a proinflammatory role during JEVinduced microglial activation. They observed nonsignificant changes in viral load after transfection with anti-miR-29b or miR29b mimic compared with JEV alone (54). Additionally, miR-451 knockdown increased IFN-b production and a panel of ISG expression during influenza infection, but it did not impact dendritic cell antiviral capacity (59).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we showed that miR-29b regulates JEV-induced expression of inducible nitric oxide synthase (iNOS) and COX-2 in BV-2 cells (19). It has previously been reported that miR-155 targets Src homology 2-containing inositol phosphatase 1 (SHIP1) to regulate the inflammatory response (20).…”
mentioning
confidence: 99%
“…Similar establishment of NF-jB dysregulation by miRNAtargeting of A20 was observed during Japanese encephalitis virus infection. This virus induced cellular miR-29b expression, which regulated A20 expression in a microglial cell line, thus enhancing NF-jB activity [61]. In stark contrast, another miRNA from the same miR-29 family, miR-29c, was found to be down-regulated in a Hepatitis B Virus (HBV)-related HCC cell line and patient samples.…”
Section: Regulation Of A20 By Micrornasmentioning
confidence: 86%